Performance Comparison Between Various Tuning Strategies: Ciancone, Cohen Coon & Ziegler- Nicholas Tuning Methods (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
This paper, explains about the background study of the coupled tank and to model such tanks using Simulink blocks. It must explains, the coupled tanks are used to select the best tuning strategy for PID controller based on its performance and stability, and then the best tuning controller is obtained after comparing various tuning strategies like Ciancone, Cohen Coon & Ziegler- Nicholas tuning methods based on their performance in controlling the couple tanks.Â The couple tank is then designed on Simulink as well and three different tuning methods for PI & PID controller calculations are implemented. The controller which gives best performance corresponding their tuning parameters which is obtained from various tuning method, and then selected.